Comparison of Blood Pressure measurements taken by one stage approach, two stage approach and digital apparatus - Kusum K; Shruti C; Ravikant; Vasantha Kalyani; Anjana Singh (Journal of Biology and Medicine - Peertechz Publications, 2019)
Mercury sphygmomanometers was developed over 100 years ago and largely unchanged since used in both hospital and ambulatory settings and considered as gold standard device for accurate blood pressure measurements. Blood pressure is important diagnostic index for circulatory function. If Blood pressure is abnormally low or high, it usually indicates greater health problem exist i.e. heart disease or stroke.So the aim of study was to compare blood pressure recordings taken with one stage approach, two stage approach and digital BP measurements among Healthy people. It was a survey approach and comparison design study were conducted and study protocol was approved by Institutional Ethics Committee.